A facelift procedure for resection of a branchial cleft cysts. Issue 2 (April 2023) - Ohta, Nobuo; Suzuki, Takahiro; Noguchi, Naoya; Shirane, Shion; Ansai, Nanako; Sato, Teruyuki; Ishida, Yusuke; Murakami, Keigo; Murakami, Kazuhiro; Nakamura, Yasuhiro
Abstract: Objectives: Branchial cleft cysts (BCCs) are common in daily practice, however, BCC patients suffer aesthetic problems due to postoperative scars on visible parts after surgery. To analyze the feasibility, surgical outcomes and possible risks and complications encountered during a facelift procedure for patients with BCC. Methods: This retrospective analysis examined patients who had undergone surgery for branchial cleft cyst using a facelift procedure (n = 16) or conventional transcervical resection (n = 20) at our institutes between April 2015 and August 2021. Results: There was no significant difference between the groups that underwent the facelift procedure or conventional transcervical resection as to the average size of the cysts, operating time, bleeding, drain out, or recurrence. None of the patients needed to switch from the facelift procedure to conventional transcervical resection. In all the patients in the facelift procedure group, postoperative scars were fully concealed by the auricle and hair. However, four patients in the facelift procedure group experienced a transient auricular complication after surgery. Conclusion: The facelift procedure provides adequate visualization, workspace and excellent cosmetic results in suitably selected cases with BCC.